Strategi Pengembangan Yogyakarta Menuju Kota Metropolitan - Hariyono, Paulus (Semarang State University, 2006)
Abstract: The Globalization of economy and informational technology has positioned the city of Yogyakarta to be swept within the current globalization. The phenomenon is felt stronger when Yogyakarta is crowned as the city of tourism, education, culture, and history. The effect of the twenty-first century's globalization area is marked with the urbanization power of centrifugal strength, which overthrows itself to the outer area of the heart of Yogyakarta City. This effect gestures the need of making an expansion to the city area, although land is limited. To solve this problem, an innovative strategy of building an urban agglomeration for Yogyakarta as a metropolitan city is devised.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â·Ã‚Â Ã‚Â Abstrak: Globalisasi ekonomi dan teknologi informasi mendudukkan Kota Yogyakarta ikut dilanda arus globalisasi. Pengaruh ini semakin kuat dengan predikat Yogyakarta sebagai kota pariwisata, pendidikan, budaya, dan bersejarah. Gejala globalisasi pada abad ke-21 ini ditandai dengan kekuatan urbanisasi yang menyerupai gaya sentrifugal yang melanting keluar pusat kota. Gejala ini mengisyaratkan perlunya perluasan kota. Sementara itu lahan Kota Yogyakarta sangat terbatas. Untuk mengatasi problematika ini, dilakukan terobosan inovatif dengan merancang Aglomerasi Perkotaan Yogyakarta sebagai kota metropolitan.Ã‚Â